Overview Studi Kelayakan Bisnis Untuk Keberhasilan Dan Keberlanjutan Usaha - Lisa Qamara; Andrian Febriansyah; Deri Kurniawan; Dini Vientiany (CV. ITTC INDONESIA, 2025)
A business feasibility study is a comprehensive evaluation process that aims to assess the potential success of a business idea before it is implemented. The process includes analyzing various aspects such as market, technical, legal, financial, and socio-economic impacts. In the market aspect, research is conducted on demand, potential market segments, and effective marketing strategies. Technical aspects include infrastructure, technology and human resource requirements. The financial evaluation examines projected revenues, costs, cash flow, and investment feasibility. In addition, the legal and socio-economic analysis highlights regulatory compliance and the impact of the business on the environment and society. The results of the feasibility study help decision-makers to assess whether the business can be continued, modified or cancelled, thereby reducing the risk of failure and maximizing the chances of success. A business feasibility study is an important tool in strategic planning to ensure a business can grow sustainably.